Comprehensive multiplatform biomarker analysis of 350 hepatocellular carcinomas identifies potential novel therapeutic options. Issue 1 (10th December 2015) - Ang, Celina; Miura, John T.; Gamblin, T. Clark; He, Ruth; Xiu, Joanne; Millis, Sherri Z.; Gatalica, Zoran; Reddy, Sandeep K.; Yee, Nelson S.; Abou‐Alfa, Ghassan K.
Abstract : Background and Objectives: Effective therapies for hepatocellular carcinoma (HCC) are limited. Molecular profiling of HCC was performed to identify novel therapeutic targets. Methods: 350 HCC samples were evaluated using a multiplatform profiling service (Caris Life Sciences, Phoenix, AZ), including gene sequencing, amplification, and protein expression. Results: EGFR, TOPO1, PD‐1, TOP2A, SPARC, and c‐Met were overexpressed in 25–83% of samples. Decreased expression of RRM1, TS, PTEN, and MGMT occurred in 31–82% of samples. TP53 was mutated in 30%, CTNNB1 in 20%, and BRCA2 in 18%; other gene mutation rates were <5%. TP53 ‐mutated tumors showed significantly higher TOPO2A (90% vs. 38%, P < 0.0001) and TS (56% vs. 29%, P = 0.0139) expression. CTNNB1 ‐mutated tumors had significantly higher AR (56% vs. 21%, P = 0.0017), SPARC (61% vs. 29%, P = 0.0135), PDL1 (29% vs. 0%, P = 0.0256) expression, and BRCA2 mutations (50% vs. 6%, P = 0.0458). Metastases exhibited significantly higher infiltration by PD‐1+ lymphocytes (79% vs. 50%, P = 0.047) and TS (31% vs. 14%, P < 0.0003) than primary HCC. Conclusions: Multiplatform profiling reveals molecular heterogeneity in HCC and identifies potential therapies including tyrosine kinase, PI3 kinase, or PARP inhibitors for molecular subtypes. Chemotherapy may benefit some tumors. CTNNB1 ‐mutated tumors may respond to multi‐target inhibition. These limited and preliminary data require clinical validation. J. Surg. Oncol. 2016;113:55–61 . © 2015 Wiley Periodicals, Inc.